Minnesota satisfaction questionnaire: psychometric properties and validation in a population of portuguese hospital workers - Martins, Helena; Proença, Maria Teresa (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Job Satisfaction has been the focus of thousands of studies and published articles in industrial-organizational psychology (Resnick & Bond, 2001). In general, Job Satisfaction is defined as a positive emotional state resulting from the appraisal of one’s job and is linked to the characteristics of one’s work (Dressel, 1982; Butler, 1990; Arches, 1991, cit in Sari, 2004), that is to say Job Satisfaction is usually treated as a collection of feelings or affective responses associated with the job situation, or “simply how people feel about different aspects of their jobs” (Spector, 1997, p.2). In 1967, Weiss, Dawis, England & Lofquist developed the short version of the MSQ - Minnesota Satisfaction Questionnaire, a 5-point Likert-type scale with 20 items. This scale has been widely used in the literature being a well-known and stable over the time instrument (cf. Mathiew and Farr, 1991, Moorman, 1993, Hart, 1999, etc. cit in Fields, 2002); previous researches have been yielding coefficient alpha values ranging from .85 to .91. This instrument is also quite parsimonious, (in comparison with the 72 items of the JDI – Job Descriptive Index, for example). In this study we developed an exploratory factor analysis to assess the factor structure of this scale in a Hospital Workers sample, with N=140, recurring to IBM – PASW. Following this procedure, we conducted a Confirmatory Factor Analysis using AMOS, where our exploratory structure was compared with other structures found in previous studies, namely Martins (2008) and Sousa, Martins and Cruz (2011). This work aims at improving our understanding of the nature and assessment of Job Satisfaction in the Portuguese health care context, providing a more stable ground for future research in this area.